Halloysite nanotubes as polyolefin fillers - Szpilska, K.; Czaja, K.; Kudła, S. (Polimery, 2015)
Halloysite nanotubes (HNTs) are a promising type of naturally occurring fillers for polymers. We review the recent progress in HNTs characterization, methods of their modification, as well as the morphology and mechanical properties of polyolefin/HNT nanocomposites. Modified HNTs well dispersed in a polyolefin matrix bring an improvement to the mechanical properties of nanocomposites. It seems that the connection of well-known advantages of polyolefins with unique properties of HNTs may result in the large-scale utilization of this type nanocomposite.